PERANCANGAN SISTEM INFORMASI PENGELOLAAN DATA ALUMNI DI SMK NEGERI 1 BUKIT SUNDI - Candra, Ade; Rini, Faiza; Kurniawan, Haris (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Data collection and storage of alumni data at SMK Negeri 1 Bukit Sundi are still not centralized. Alumni data of SMK Negeri 1 Bukit Sundi are spread across various storage media, such as in paper documents, ledgers and storage on computer devices. Data storage that is still in paper form causes the data search process to take a long time. This study aims to build an alumni data management information system that can carry out the process of recording alumni data and the process of disseminating information related to alumni. The system design uses the Software Development Life Cycle (SDLC) method with the Aqile model. The system flow design uses the Unified Modeling Language (UML). The results of the study are in the form of a website-based alumni data management information system. The alumni data management information system can function properly so that it can be used by SMK Negeri 1 Bukit Sundi in assisting the process of recording and informing alumni data of SMK Negeri 1 Bukit Sundi